Assessing the robustness of vascular surgery meta-analyses using the Fragility Index: a cross-sectional study - Yi Guo; Wei Lu; Qiang Hu; Tiehao Wang; Chengxin Weng; Jiawen Wu; Jiacheng Li; Lihong Lin; Guobing Cheng (BMJ Open)
Objectives To systematically assess the robustness of meta-analyses based on randomised controlled trials (RCTs) in vascular surgery using the Fragility Index (FI).Design Cross-sectional study.Setting Meta-analyses published in English from January 2019 to April 2025, identified from EMBASE, PubMed and Web of Science.Participants 67 articles, with 291 meta-analyses involving RCTs evaluating vascular surgical interventions, covering venous, aortic, peripheral arterial, vascular access and other relevant fields.Main outcome measures FI, defined as the minimum number of event changes required to alter the statistical significance of meta-analysis results, and its association with sample size and total number of events, analysed using frequency distribution histograms and restricted cubic spline models.Results The median FI was 7, with considerable variation across different fields. Aortic meta-analyses demonstrated higher robustness compared with venous and vascular access meta-analyses. FI showed a non-linear relationship with sample size and total number of events, indicating robustness improved only up to specific thresholds, beyond which robustness declined or plateaued.Conclusion Overall robustness of meta-analyses in vascular surgery was moderate, with notable variability among research areas. FI provides valuable insight into the stability of synthesised evidence, suggesting the need for improved methodological quality and advocating broader adoption of FI in meta-analytical research.